Marquise De Ganges : Celebrated Crimes - Dumas, Alexandre, 1802-1870 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Marquise De Ganges" by Alexandre Dumas is a historical novel likely written during the late 19th century. The story revolves around the tragic life of Marie de Rossan, who became the Marquise de Ganges, and explores her beauty, tumultuous relationships, and the ominous predictions surrounding her fate. The novel encapsulates themes of love, jealousy, and betrayal set against the backdrop of the court in 17th-century France. At the start of the narrative, we are introduced to a faceless woman visiting a sorceress in Paris, seeking insight into her future. This leads to a prophecy that predicts her beauty and youth but also forewarns of a violent death. The woman is revealed to be Marie de Rossan, later known as the Marquise de Ganges. Following her tumultuous marriage to the Marquis, with whom she initially shares a tender bond, the dynamics change drastically due to jealousy and manipulation from her brothers-in-law. As the story unfolds, hints of tragedy loom over Marie$1 (Bs life, reflecting on themes of fate and the perils of desire, leading to a narrative steeped in dramatic events and emotional turmoil. (This is an automatically generated summary.)s
Release date is 2004-09-22
Produced by David Widger
Keywords: Crime